Study on the effect of modified clay on algae-derived organic nitrogen mineralization and its mechanisms in diatom Skeletonema costatum - Xin Feng; Wentao Wang; Wentao Wang; Wentao Wang; Yongbao Chu; Jianan Zhu; Jianan Zhu; Lianbao Chi; Lianbao Chi; Jing Chen; Jing Chen; Jing Chen; et al. (Frontiers in Marine Science)
Algae-derived organic nitrogen (AON) is mineralized by microorganisms to bioavailable inorganic nitrogen form, potentially sustaining the harmful algal blooms (HABs) for extended durations. The modified clay (MC) is an effective approach for mitigating HABs; however, its effects on the AON mineralization and the underlying mechanism remain unclear. In this study, the effects of MC on the mineralization of AON by a typical HAB species Skeletonema costatum were analyzed using the isotope dilution method, and the underlying mechanism were preliminarily discussed. The results revealed that the addition of MC could reduce the mineralization rates of AON and the regeneration amount of inorganic nitrogen by 71% and 60%, respectively, compared to the control group. The total fluorescence intensity was approximately 46% lower than that of the control group. In addition, the bacterial proliferation was suppressed by 66% and the community evolved from uniformity to diversification. It is hypothesized that the physical encapsulation of AON, chemical bonding of molecules and the variations of the microbial community under the utilization of MC were key mechanisms influencing the mineralization process. This study offers valuable insights into the environmental impacts following the HABs management and provides a scientific basis for investigating the controlling mechanisms of marine organic matter mineralization and burial.